Social Media's Impact on Global Purchasing Decisions via Key Insights: Dampak Media Sosial terhadap Keputusan Pembelian Global melalui Wawasan Utama - Sakdiyah , Ni’matus; Fitriyah, Hadiah (Indonesian Journal of Innovation Studies, 2024)
This study examines the influence of social media on purchase decisions, focusing on entertainment, trendiness, and electronic word of mouth (E-WOM), with follower count as an intervening variable. Conducted on followers of the "SECACA.ID" social media account, the research utilized a quantitative approach with 100 respondents. Results indicate that entertainment significantly affects purchase decisions independently, while trendiness influences both directly and indirectly. E-WOM requires follower count as an intervening variable to impact purchase decisions. The findings suggest businesses focus on enhancing content quality and attractiveness on social media to influence consumer behavior positively, considering follower count as well. Further research with larger samples and broader contexts is recommended to validate and extend these findings. Highlight: Entertainment Directly Affects Purchases Follower Count Moderates E-WOM Impact Enhance Content Quality for Better Influence Keywords: Social media, Purchase decisions, Follower count, Entertainment, E-WOM